Beyond the "formidable circle": Race and the limits of democratic inclusion in Tocqueville's Democracy in America - HENDERSON, Christine Dunn (Institutional Knowledge at Singapore Management University, 2021)
Despite his assertion that the first volume of Democracy in America (1835) would concentrate upon institutions, Tocqueville found himself finishing the draft manuscript in 1834 and unable to conclude his study without discussing race relations in the United States. In the end, he quickly penned a final chapter. That chapter—by far the book’s longest—offers “Some Considerations on the Present State and Probable Future of the Three Races That Inhabit the Territory of the United States.” Tocqueville begins the chapter by acknowledging that its subject “is American without being democratic” (DA, p. 516), and to the extent that it analyzes slavery in the South and the interactions of the Native Americans with the Anglo-European white Americans, this is true. When read in the context of his broader analyses of the psychology of equality, of majoritarian power, and of the importance of mores over laws, however, Tocqueville’s analysis of black–white race relations goes beyond its American context to offer an examination of the extra-legal barriers to inclusion and membership within a liberal democracy. As such, it offers a critical perspective on democratic theory, by suggesting that there are certain types of exclusions that cannot be resolved through formal institutions or by reformed processes of democratic deliberation.